Adaptive Learning Media within Universal Design for Learning: A Systematic Literature Review for Supporting Slow Learner Students - Hutapea, Kitaman; Marmoah, Sri; Azman, Mohamed Nor Azhari (Universitas Sebelas Maret, 2026)
Inclusive education has become a global priority in ensuring equitable access to quality learning by promoting flexible, accessible, and student-centered approaches that address the diverse needs of all learners, including slow learner students. Slow learner students often face difficulties in conventional learning due to their diverse learning needs, thus requiring inclusive approaches such as Universal Design for Learning (UDL) and flexible, personalized adaptive learning media to meet individual needs. This study aims to systematically review the literature on the use of adaptive learning media within the UDL framework to support the learning needs of slow learner students. The review was conducted using the PRISMA model by analysing articles indexed in SINTA, Scopus and proceeding over the past ten years from 2016-2026 to identify types of media, UDL implementation, and their impact on learning outcomes. The findings indicate the review of 30 studies shows that adaptive learning media particularly audio-visual, manipulative, and visual forms are widely used to support slow learner students, with a strong emphasis on mathematics and language learning. These media effectively enhance understanding, engagement, and individualized learning in line with UDL principles, although the implementation remains more focused on representation and engagement than on action and expression.